Effect of lipstick on composite resin color at different application times - Avilmar Passos Galvão; Letícia Borges Jacques; Luciana Dantas; Paula Mathias; André Mallmann (University of São Paulo, 2010)
OBJECTIVES: The aim of this study was to evaluate the influence of the contact of two lipsticks, one with common fixer and one with ultra fixer, on the color of a composite resin immediately, 30 min and 24 h after photoactivation. MATERIAL AND METHODS: Ninety specimens were prepared with a composite resin, Filtek-Z350. Specimens were polished and divided into 9 groups (n=10) according to time elapsed after photoactivation (A- immediately; B- 30 min; C- 24 h) and the contact with lipstick (UF- lipstick with ultra fixer; F- lipstick with common fixer). The control group was represented by specimens that did not have any contact with lipstick (C- without lipstick). Color measurements of the specimens were carried out using a spectrophotometer (Easyshade - CIE L* a* b* system). For UF and F groups, the baseline color of the specimens was measured immediately before pigmentation and the lipsticks were applied dry after 1 hour. The excess lipstick was removed with absorbent paper and final color checking was performed, including the control group. Differences between the final and baseline color measurements were calculated and data were analyzed statistically by the Kruskal-Wallis test at 5%. RESULTS: The means between the differences of color values were: AUF: 16.0; AF: 12.4; AC: 1.07; BUF: 9.51; BF: 8.3; BC: 0.91; CUF: 17.7; CF: 12.41; CC: 0.82. CONCLUSION: Groups where lipstick was applied showed greater staining than the control group at the three evaluation times. The lipstick with ultra fixer stained more than the lipstick with common fixer. Time elapsed between photoactivation and contact with lipstick had a similar influence on the groups that received lipstick application.